2017
DOI: 10.1186/s13071-017-2386-z
|View full text |Cite
|
Sign up to set email alerts
|

Sand fly and Leishmania spp. survey in Vojvodina (Serbia): first detection of Leishmania infantum DNA in sand flies and the first record of Phlebotomus (Transphlebotomus) mascittii Grassi, 1908

Abstract: BackgroundLeishmaniasis in Serbia was an endemic disease, and is considered to be eradicated for more than 40 years. In the past decade sporadic cases of canine leishmaniasis started to emerge for the first time in Vojvodina Province (previously non-endemic region of Serbia). Reports of introduced, and later on autochthonous cases of leishmaniasis alerted the possibility of disease emergence. The aim of this study was to bridge more than a half a century wide gap in entomological surveillance of sand fly vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…The detection of different Leishmania spp. in non-competent vectors has been previously reported [38][39][40].…”
Section: Discussionmentioning
confidence: 86%
“…The detection of different Leishmania spp. in non-competent vectors has been previously reported [38][39][40].…”
Section: Discussionmentioning
confidence: 86%
“…A recent study in Serbia, central Europe, showed the emergence of sporadic human and canine leishmaniasis cases in the country which were confirmed by entomological surveillance by the presence of Leishmania spp . in sand flies with an infection rate of 4% [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The sandfly population collected from the island of Leros was composed of 10 species, with P. papatasi, P. neglectus and P. tobbi being the most dominant, followed by S. minuta and P. simils , representing the sandfly fauna on the island of Leros, Greece. Previous studies in Serbia, Albania and other countries in the East Mediterranean basin have shown similar sandfly species distribution with P. neglectus most often identified as the dominant species [ 7 , 8 , 9 , 10 ]. A recent study in the same study region in Greece reported P. neglectus as the predominant species, followed by S. minuta, P. tobbi, P. simici and P. similis [ 12 ], which were also detected in our study.…”
Section: Discussionmentioning
confidence: 65%
“…Collective field studies in the Mediterranean region [ 7 ] and neighboring countries like Albania [ 8 ] and Serbia [ 9 , 10 ], verified the presence of several Phlebotomus species like P. neglectus, P. tobbi, P. balkanicus, P. ariasi, P. perfiliewi, P. perniciosus, P. kandelakii, P. mascitii, P. alexandri, P. sergenti. P. similis, P. simici, P. patasi, all being proven or potential vectors of Leishmania .…”
Section: Introductionmentioning
confidence: 99%